e-Government and Employment Services A Case Study in Effectiveness - Fugini, Maria Grazia; Maggiolini, Piercarlo; Valles, Ramon Salvador; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book explores the factors that affect the efficiency and effectiveness of electronic government (e-Government) by analyzing two employment- service systems in Italy and Catalonia: the Borsa Lavoro Lombardia Portal (Lombardy Employment Services Portal) and the Servei d’Ocupació de Catalunya (Catalan Employment Services Portal). The evaluation methodology used in the case studies and the related set of technical, social, and economic indicators are clearly described. The technological and organizational features of the systems of the two systems are then compared and their impacts assessed. In addition, the extent to which each system has been a driver of employment within its region and country is evaluated in relation to the impact of the industrial and commercial background. Readers will gain a deeper understanding of the main factors that might influence the effectiveness of e-Government and appreciate how the use of information and communication technology (ICT) may appear to improve the execution of government functions yet not achieve a true increase in effectiveness.  .
Introduction -- Framework -- Evaluation Methodology -- Employment Services in Catalonia -- Borsa Lavoro Lombardia -- Comparisons and Concluding Remarks.
Keywords: Application software; Personnel management; Quality of life; Computer Appl. in Social and Behavioral Sciences; Human Resource Management; Quality of Life Research; Information Systems Applications (incl. Internet).